(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: The most impacted people are those with chronic liver disease (CLD) and acute kidney injury (AKI), who have the largest proportion of such complications. The presence of AKI in such patients has a considerable effect on their survival. Furthermore, renal failure is directly associated with hepatic dysfunction in CLD patients, and this association is complicated, with various factors contributing to it, including infection, underlying renal disease, and the occurrence of hepatorenal syndrome. Objective: To determine the rate of cases of acute kidney injury (AKI) among chronic liver disease patients who visit Jinnah Postgraduate Medical Center (JPMC), Karachi, and the risk factors. Methods: It was a cross-sectional study that was carried out in November 2024- April 2025 and included 150 CLD patients. The clinical and laboratory data and incidence of AKI were examined. KDIGO has been used to define AKI. Findings: A case rate of AKI amongst CLD patients was found to be 26.7 percent. The most relevant etiological factors were determined to be infection, nephrotoxic drugs, and hepatorenal syndrome. Conclusion: Acute kidney injury is prevalent among people with chronic liver disease, and early detection and intervention of the disease play significant roles in improving the prognosis of the patients.